REPRESENTASI MATEMATIS SISWA KELAS XII IPA SMA NEGERI 1 KABUPATEN MAGETAN DALAM PEMECAHAN MASALAH TRIGONOMETRI DITINJAU DARI KOMPETENSI PENGETAHUAN - mashuri, anwas (Indonesian Journal Of Education and Learning Mathematics, 2020)
ABSTRACT: This research aimed to analyse verbal, visual,and symbolic mathematical representations abilities for students for 12th natural-science grade SMA Negeri 1 Kabupaten Magetan in solving trigonometric problems viewed from high competence of knowledge. This research used qualitative method. The participants were 4 students who had high competence of knowledge taken from 20 students of 12th natural-science grade SMA Negeri 1 Kabupaten Magetan, Jawa Timur. Data validation was carried out using time triangulation. Data analysis used Huberman and Miles stages. The results showed that participants answered not only based on the given figure, but also used the definition of trigonometric ratio on verbal representations. On the other hand, paricipants were able to determine the object positions to be observed. However, paricipants failed to determine the direction of the angle of depression at the sketches made on visual representations. Failure in determining the direction of the angle of depression to cause an error in using the mathematical equation properly. Finally, participants were unsuccessful to use the mathematical equation properly on symbolic representations. From this research, we could recommend the importance of translations between mathematical representations and mathematical problems, as well as translations among mathematical representaions (verbal, visual, and symbolic) in learning mathematics in the classroom. Keywords: Competence of Knowledge, Mathematical Representations, Trigonometric Problems